2004
DOI: 10.2320/matertrans.45.1859
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction Equilibria of FeCl<SUB>3</SUB> with TBP

Abstract: Solvent extraction equilibria of FeCl 3 with TPB from chloride solutions were analyzed by considering chemical equilibria, extraction reaction, mass and charge balance equations. The activity coefficients of solutes in aqueous phase were calculated by Bromley equation while ideal behavior was assumed for species in organic phase. Extraction reaction of FeCl 3 with TBP in the experimental range of this study was determined from the dependence of the distribution coefficient of iron on the concentration of chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…TableS3(Supporting Information) indicates that the distribution coefficient of iron (D Fe ) increased with increasing concentrations of HCl, FeCl 3 , and TBP. The predictions obtained using the present methodology are comparable to the published data1 and exhibit good agreement with the experimental data, as shown in Figure3. In our system, iron does not exist in both phases in the same form, and consequently, the definition of the distribution coefficient of iron (D Fe ) is considered as= = • • D (iron concentration in the organic phase) (iron concentration in the aqueous phase) [FeCl HCl 2TBP] [iron present in the aqueous phase in all forms]…”
supporting
confidence: 87%
See 2 more Smart Citations
“…TableS3(Supporting Information) indicates that the distribution coefficient of iron (D Fe ) increased with increasing concentrations of HCl, FeCl 3 , and TBP. The predictions obtained using the present methodology are comparable to the published data1 and exhibit good agreement with the experimental data, as shown in Figure3. In our system, iron does not exist in both phases in the same form, and consequently, the definition of the distribution coefficient of iron (D Fe ) is considered as= = • • D (iron concentration in the organic phase) (iron concentration in the aqueous phase) [FeCl HCl 2TBP] [iron present in the aqueous phase in all forms]…”
supporting
confidence: 87%
“…This choice was motivated by the fact that this is a well-understood system. 1 The main intention was to model the reactive extraction system (FeCl 3 with TBP) without a constraint on the initial guesses for predicting liquid−liquid equilibria. Here, we used the reaction equilibria and thermodynamic values from Lee et al, 1 as indicated in Table S1 of the Supporting Information.…”
Section: Solvent Extraction Equilibria Of Fecl 3 With Tbpmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In the case of separation of ferric iron by amines or TBP, strong HCl solution is needed, while moderate acidity is enough to selectively extract ferric iron by cationic extractants. 1,5,8 Among the extractants mentioned above, extraction of Fe(III) by D2EHPA has been extensively investigated. Difficulties have been reported in the stripping of Fe(III) from the loaded D2EHPA even with concentrated acid.…”
Section: Introductionmentioning
confidence: 99%
“…Ferric iron has a strong tendency to form complexes with chloride ion which can be extracted selectively by amines 1,2 and TBP. [3][4][5] Moreover, there is some difference in the value of pH 50 (the pH at which 50% of the metal is extracted) by cationic extractants [6][7][8][9] among Co(II), Fe(III), Mn(II) and Ni(II). 10 In the case of separation of ferric iron by amines or TBP, strong HCl solution is needed, while moderate acidity is enough to selectively extract ferric iron by cationic extractants.…”
Section: Introductionmentioning
confidence: 99%